QUESTIONING ZAKAT PROFESSION AND ITS CONTROVERSIES IN THE CONTEMPORARY ERA (IAIN PONOROGO, 2022)
Kajian ini bertujuan untuk menjelaskan hal-hal mendasar terkait keberadaan zakat profesi dan membahas berbagai konsekuensi zakat di era kontemporer. Metode penelitian yang digunakan adalah studi literatur. Hasil penelitian menunjukkan bahwa zakat profesi merupakan hal yang baru dimana jenis zakat ini belum pernah ada sebelumnya di masa Nabi. Zakat ini diketahui baru muncul pada abad ke-20 dengan digagas oleh salah seorang ulama kontemporer, Yusuf Qardhawi, melalui karyanya yang berjudul Fiqh Az-Zakat. Munculnya zakat memicu berbagai pro dan kontra, terutama dari berbagai ulama fikih modern. Sebagian ulama kontemporer menentang keberadaan zakat ini karena dianggap tidak pernah dicontohkan oleh Rasulullah, juga tidak memiliki dalil dan nash yang jelas. Di sisi lain, pendapat ulama yang mendukung zakat dalam profesi ini didasarkan pada penafsiran pemotongan Q.S Al-Baqarah ayat 276 tentang kewajiban memberikan sebagian dari hasil usaha yang wajar. Ada beberapa perbedaan pendapat tentang penanaman zakat dalam profesi ini, antara lain zakat pertanian, zakat emas, zakat perdagangan, dan zakat rikhaz. [This study aims to review essential matters related to the existence of professional Zakat and the various controversies that cover Zakat in the contemporary era. The research method used is a literature study. From the study results, it is known that professional Zakat is a new case where this type of Zakat never existed before in the time of the Prophet. This Zakat is known to have only emerged in the 20th century with the idea of a contemporary scholar, Yusuf Qardhawi, through his work entitled Fiqh Az-Zakat. The emergence of Zakat has triggered various pros and cons, mainly from various modern fiqh scholars. Some contemporary scholars oppose the existence of this Zakat because they are considered to have never been exemplified by the Prophet and do not have clear arguments and texts. On the other hand, the opinion of scholars who support professional Zakat is based on the interpretation of the excerpt of Q.S. Al-Baqarah verse 276 regarding the obligation to pay Zakat on a portion of the results of a good business. There are several differences of opinion regarding the analogy of Zakat in this profession, which include the metaphor of Zakat on agriculture, Zakat on gold, Zakat on trade, and Zakat on wealth.]